Personal Adjusment of Female Students from Eastern Indonesia at Satya Wacana Christian University - Angeliq Shareen Noya; Wahyuni Kristinawati (Journal La Sociale, 2024)
This qualitative research aims to understand the adaptation process of female students hailing from Eastern Indonesia in the environment of Satya Wacana Christian University. The study explores various aspects of self-adjustment, including internal motivation, involvement in student activities, cultural adaptation skills, and the social support they receive. The research employs in-depth interviews and content analysis of data obtained from female Eastern Indonesian students who have relocated to the university. The findings reveal that internal motivation plays a significant role in encouraging Eastern Indonesian female students to migrate and actively participate in campus life. Involvement in student organizations with similar cultural backgrounds accelerates both academic and social adjustment. Adaptation skills in a cultural context, including the ability to adapt to new languages and cultures, enable students to build close social relationships and boost self-confidence. Social support from peers with similar cultural backgrounds also provides crucial assistance in overcoming challenges and difficulties in adaptation. However, the research also identifies several challenges, such as language and communication difficulties, as well as pressure to conform to group norms. The findings of this study can offer valuable insights for educational institutions and policymakers to develop more effective support programs for female students originating from Eastern Indonesia in the university environment.